2018
DOI: 10.1080/19386362.2018.1473195
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of sequential active and passive arching in granular soils

Abstract: Arching in soils has received great attention for several decades due to its significance on the soil-underground structure-interaction. However, soil layers underneath such an underground structure might undergo cycles of swelling and shrinking resulting in the generation of alternating active and passive modes of soil-underground structure-interaction. Consequently, the stresses on the underground structure and adjoining regions of ground become complex. The state of stress on underground structures as a res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…For trapdoor problem, K is not easy to be determined as stress transfer and principle stress rotation with trapdoor movement. Different researchers have proposed different methods to determine K values in both active and passive states [1,8,18,44]. However, most of the method only provide a constant value of K. In this part, Different from previous methods, considering K may change as the trapdoor moving, each ratio q is related to the K at that stage.…”
Section: Initial Cyclementioning
confidence: 99%
See 1 more Smart Citation
“…For trapdoor problem, K is not easy to be determined as stress transfer and principle stress rotation with trapdoor movement. Different researchers have proposed different methods to determine K values in both active and passive states [1,8,18,44]. However, most of the method only provide a constant value of K. In this part, Different from previous methods, considering K may change as the trapdoor moving, each ratio q is related to the K at that stage.…”
Section: Initial Cyclementioning
confidence: 99%
“…The alternant active and passive trapdoor problem was first investigated by Aqoub et al [1]. This study mainly focused on the load evolution of sequential active and passive arching and found that the alternation of the movement direction was detrimental to formation of full active and passive arching.…”
Section: Introductionmentioning
confidence: 99%
“…The interactions of buried structures, thin overburdened soils, and high-load frequencies accelerated soil arching degradation and led to greater surface settlement. Some structures produce passive arching effects in many engineering applications, such as grillage foundations [34,35], cluster piles [36,37], and buried steel culverts [38]. Xiang REN et al and Ma D et al [39,40] studied the formation process and influence factors of passive soil arching before cantilever anti-slide piles through numerical modeling.…”
Section: Introductionmentioning
confidence: 99%
“…For embankments, for example, the typical movement due to self-weight is 0.1% of the height of the embankment (Look, 2007). Other examples of passive arching include pile groups, where a pile may experience both active and passive arching on different sides (Shelke and Patra, 2008;Yuan, et al, 2014), anti-sliding or D r a f t stabilisation piles inserted into soil slopes (Chen and Martin, 2002;Kahyaoğlu et al, 2012;He et al, 2015), swelling of soil around an underground structure (Aqoub et al, 2018), or even soil pressure sensors where over-registration of stress values indicate passive arching on the sensor (Talesnick, 2013).…”
Section: Introductionmentioning
confidence: 99%